Community Financing of School Transport and Travel and its Effects on Quality Secondary Education in Kisumu County, Kenya - Duncan Otieno Owiye; Maureen Olel; James Ochieng Sika (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2024)
Effectiveness of public financial support for secondary education is an issue of concern given the delay in submitting government grants, challenges of increased enrolment and inadequate resources to support quality teaching and learning. The Free Day Secondary Education Policy was implemented in 2008 with an aim of making secondary school education available and affordable to school going children regardless of their social class. In achieving equity, enrolment increased the inadequacy to sustain secondary schools towards achieving quality education. Kisumu County was chosen for its below average KCSE mean score of 4.08 (D+) in 2017 compared to the average mean of 6 (C); low teacher student ratio at 1:59 compared to the required 1:45 and absolute poverty index of 41% compared to the national poverty index of 35.6. The purpose of this study was to analyze community financing of public secondary schools and its effect on quality of education in Kisumu County, Kenya. It was guided by the following objective: community financing of secondary school transport and local travel of students and its effect on provision of quality education in Kisumu County.A descriptive and correlation research design was used in the study. The target population for this study comprised of 214 Secondary schools in Kisumu County, 214 school principals, 214 BOM chairpersons, the CDE, 48 CBOs and 50,243 students. Questionnaires, document analysis and interview schedule for school principals, BOM chairpersons, the CDE, CBOs and students were used in this study. Stratified simple random sampling procedure was used to sample the 64 public secondary schools in Kisumu County from which 64 school principals, 64 BOM Chairpersons, 16 CBOs and 387 purposively selected students were used for the study. Piloting of instruments was done in six schools. Content and face validity of the instruments were determined by employing experts in the department of education management and foundations. Reliability of the instruments was calculated by using the test re- test and was calculated at Pearson r coefficient of 0.879. The results showed that community financing transport, travelling and academic performance had a strong positive correlation of 0.919. The study concluded that community financing of adequate educational resources significantly influences the academic performance of learners to a great extent. The study recommended Free Day Secondary Education funding should be increased in order to achieve fully the objectives of the secondary education policy. The findings may be significant to policy makers, education planners and implementers on the requirement for the registration of institutions of higher learning.